REFLECTION OF NATURE AND LOVE IN THE POETRY OF ASKAR MAHKAM (TAMADDUN NURI JURNALI, 2025)
This article is dedicated to analyzing the artistic depiction of nature and love in the poetry of Asqar Mahkam. In his works, nature is portrayed not only as a source of beauty but also as a symbol reflecting the human Inner world and philosophical views. Love, depicted as the highest expression of human emotions, is harmoniously intertwined with nature. The article explores the interconnection between the depiction of nature and love, highlighting the poet’s artistic mastery, imagery, and philosophical approach